Improving Students' Writing Ability Through Image Media in Class II Students of UPTD SDN 35 Barru - Tarman, Tarman; Tulmunawwara, Madinah; Tunny, Chairul Agung; Jusman, Zulhaj (Jurnal Ilmiah Mandala Education (JIME), 2025)
This study aims to improve students' writing skills through image media by using an individual learning learning model in class II UPTD SDN 35 Barru. This research is Classroom Action Research, the subject of this study is class II which amounts to 15 students consisting of 8 boys and 7 girls. This research was carried out as many as 2 cycles, each cycle consists of four stages, namely action planning, action implementation, evaluation, and reflection. This research was conducted in the Teacher Training Professional Strengthening (P2K) activity which began on September 15-Augustus  in the 2023/2024 school year. The results showed that the average score (mean) after applying image media in learning increased from 78% to 82%. Similarly, the completeness of student learning has increased from cycle I and cycle II. And from the results of the comparison of learning process activities in cycles I and II showed that there were several student activities that increased such as student attendance, students who paid attention to material discussion, students who asked questions and students who did practice questions. So it can be said that through image media can improve writing skills and learning outcomes of grade II students of UPTD SDN 35 Barru.